Konceptutveckling av träningshjälpmedel för elitsimmare - Sandvik, Daniel; Gullberg, Ida (2011)
This abstract describes a subproject which main target is to develop a training device for elite swimmers. The work is a masters thesis at the Master programme in Industrial Design Engineering at Luleå University, carried out from fall 2010 to spring 2011. The sub-project is part of a larger project, named Trainerkoll, and is one part of three sub-projects, marketing, engineering/electronics development, and concept development.Our part of the project; concept development, will be the preparatory work and base for the other two sub-project. "Trainerkoll" was started by the project owner and innovator Ola Wallberg, with the aim of developing a new product which was supposed to eventually be the start of a new company.The target group range from early youth elite swimmers to more active in the so- called Masters Series. It involves a wide range of users, despite the focus on elite swimmers.The idea that formed the basis for this development was to improve the possibility to measure time, heart rate, lactate and also making it possible to communicate with the swimmer during a swim session. At the current situation focus is at counting the arms frequency, number of lengths, or keep track of the times, when the focus really should be on the technique of swimming. In addition to this products included in the main project, a handheld device for communication, and a Web service for active analysis of the collected data are included.Our project started with the analytical phase in which the information was collected by analyze the current situation by benchmarking competing products, existing surrounding technologies and related products. Interviews were made with swimming coaches during a visit at Eriksdalsbadet in Stockholm, and we also visited the physiological test center Winternet in Boden.This phase resulted in ideas regarding the needs and preferences, and was an important basis for further development. Among other things, we found a clearly demand to improve the timing system during training, and also a need for ...